Applicability of the Willems method of estimation of dental age for the population of Brazil - Chuquimarca Loor, Ronald Andres (2021)
Introduction: Dental development is used to assess maturity and predict dental age in the dental clinic. This information helps in diagnosis, planning and treatment. To verify the dental development of 76 untreated children between 6 and 13 years of age, they were evaluated using the Demirjian Method or Willem\'s technique, using 76 panoramic radiographs from the collection of the orthodontic discipline of the Faculty of Dentistry of Bauru - University of São Paulo. In the absence of studies in South America using this technique, the study was carried out so that children were classified by sex and age, to estimate dental age and to compare it with chronological age and to describe the formation of permanent mandibular teeth in Brazilian population. Objective: To evaluate the applicability of the Willems dental age estimation method in untreated Brazilian youngsters aged 6 to 13 years using panoramic radiographs, quantifying the variations between chronological ages. Material and Methods: The sample consisted of 76 panoramic radiographs of untreated youngsters from the collection of Discipline of Orthodontics, Faculty of Dentistry of Bauru, divided into two groups: group 1, retrospective sample consisting of 44 panoramic radiographs between 6 and 13 years old for women, and group 2, a retrospective sample consisting of 32 panoramic radiographs between 6 and 13 years old for men. The dependent t test was used to assess the systematic error and the Dahlberg formula for the casual error. The normal distribution of the samples was assessed by the test t for paired groups, followed by the Mann-Whitney test. Conclusion: Dental age, according to the method of Willem et al, proved not to be a good indicator of chronological age, giving us an overestimation in our sample, which can be considered a partial invalid test in the population of Brazilians, both sexes.